Merchants cross Raton Pass in business ventures - Donachy, Pat (Raton, NM Raton Range, 1992)
Article is about shoppers from the surrounding areas supporting businesses in Raton and Trinidad.
Newspaper article + photograph of Robert Dixon
Master list item #: 62
File location is in the Raton file Cabinet
Keywords: Terry, Kathy -- Manager of Teri's Hallmark in Raton; Marco -- Manager of Teri's Hallmark in Trinidad; Garcia, Charles -- Raton Optical Outlet; Dixon, Bob -- Accountant; Duran, J. R. -- Owner of J.R.'s country Store; Lackey, Howard -- Owner; Teri's Hallmark -- Trinidad, Colorado -- Raton, New Mexico; Optical Outlet -- Trinidad, Colorado -- Raton, New Mexico; Dixon, Waller and Company CPAs -- Trinidad, Colorado -- Raton, New Mexico; McDonald's Restaurant -- Trinidad, Colorado -- Raton, New Mexico; Dairy Queen -- Trinidad, Colorado -- Raton, New Mexico; J. R. 's Country Store -- Trinidad, Colorado -- Raton, New Mexico; United Chevrolet -- Trinidad, Colorado; Raton, New Mexico; Circle Chevrolet and Buick -- Trinidad, Colorado; Local Businesses; Colorado Businesses; New Mexico Businesses; Trinidad Shoppers; Raton Shoppers; Trinidad, Colorado; Raton, New Mexico